Chronic Pericardial Hematoma with Suppression of the Right Ventricle: A Rare Complication of a Coronary Artery Aneurysm - Schlömicher, Markus; Haldenwang, Peter Lukas; Reichert, Josef; Moustafine, Vadim; Bechtel, Matthias; Strauch, Justus Thomas (The Thoracic and Cardiovascular Surgeon Reports, 2014)
We present a case of a 67-year-old patient referred to our department with a pericardial mass lesion measuring 11 × 4 × 7.5 cm as diagnosed in computed tomography scan. The patient showed a history of progredient dyspnea. Video-assisted thoracoscopy as well as an explorative full sternotomy to resect the mass lesion had been performed at the referring hospital subsequently before admission to our department. Intermittent hemodynamic instability caused the procedure to stop and a transfer to the cardiothoracic surgery department, following which a resternotomy was performed. Inspection of the surgical site and subsequent intraoperative rapid section revealed an old organized and dense pericardial hematoma adherent to the right ventricle. The suspicion of covered coronary artery perforation led to an intraoperative coronary angiography, which revealed a large proximal coronary aneurysm of the right coronary artery and a subtotal stenosis of the circumflex branch. The hematoma could be removed with decompression of the right ventricle under cardiopulmonary bypass conditions. The further postoperative course was uncomplicated with retransfer to the referring hospital on the postoperative day 8.
Keywords: aneurysm; thoracic surgery